An introduction to social policy - Peter Dwyer
Includes indexes.; This book aims to introduce students to the study of social policy by offering an accessible consideration of certain key concepts, themes and contemporary issues and debates; CX032 An sinh xã hội ; CX010 An sinh xã hội ; CX011 Chính sách xã hội